Exploration of Students’ Knowledge about Predicate and Tree Construction in Syntax - Tarigan, Najwa Ramadhani; Luthfi, Jihan; Farhansyah, Qoeddri; Ismahani, Siti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
English language instruction places a high priority on syntax, notably in assisting pupils in comprehending grammatical relationships and sentence structure. Predicate identification and syntax tree creation, both of which demonstrate students' comprehension of hierarchical sentence structures, are two crucial aspects of syntax learning. This study seeks to determine how well students comprehend predicate identification and syntax tree creation in English syntax. Students in the English Department who had finished a syntax course participated in a quantitative descriptive study design. The data were gathered via an internet survey that included Likert scale questions and multiple-choice options. The data were then analyzed using descriptive statistics presented as percentages. According to the data, the majority of students exhibit a strong conceptual grasp of predicates, as seen by their capacity to recognize predicates in basic sentences and identify verbs as the head of verb phrases. But in analyzing complex sentence structures and building syntax trees, students exhibit less assurance and skill. Despite these challenges, students show a positive outlook on learning syntax and a strong desire to increase their knowledge. The research comes to the conclusion that, despite students having basic syntactic knowledge, more instructional focus should be placed on visual-based methods and guided practice in order to improve their practical skills in creating syntax trees.